Investigating the impact of user perception and gamification elements on repurchase decisions in game live broadcasting - Zhang, Guihua; Cao, Junwei; Huang, Mengli; Meng, Shang (Frontiers in Psychology, 2025)
As a branch of online live broadcasting, the development of game live broadcasting is also getting faster and faster. Based on the theory of affordance-psychological outcome-behavioral (A-P-B), this paper introduces three gamification elements of user activity visibility, user level visibility and purchase effect visibility, and three user-perceived experience values of perceived hedonic value, perceived cognitive value and perceived social value to establish the model. After collecting data through questionnaires, an empirical analysis based on partial least squares structural equation modelling (PLS-SEM) was carried out using SPSS and SmartPLS data analysis methods to explore the influencing factors of viewers’ re-purchase behaviors in game live broadcasting from the perspective of the visibility of gamification elements. The results of this study show that in game live broadcasting, there is a certain influence between the visibility of gamification elements and the perceived value of users, and that the visibility of user activity, the visibility of purchasing effects, and the visibility of user level all have a significant positive effect on the perceived value of the user experience. This study enriches the literature on the business aspects of game live broadcasting and consumer behavior and has a certain significance in guiding live broadcasting business scenarios to improve the re-purchasing behavior of live broadcast viewers.